Frequency of arrhythmias and other cardiac abnormalities in fulminant hepatic failure. Issue 11 (November 1976) - Weston, M J; Talbot, I C; Horoworth, P J; Mant, A K; Capildeo, R; Williams, R
Abstract : In a series of 106 patients with fulminant hepatic failure and grade 4 encephalopathy, cardiac arrhythmias and other abnormalities occurred in 92 per cent. The most common was sinus tachycardia (75%) and this was the only abnormality in 22 per cent of the patients. Sudden cardiac arrest occurred in 25 per cent, various ectopic beats in 20 per cent, and heart block or bradycardia in 18 per cent. Other electrocardiographic abnormalities, mostly of the T wave and ST segment, were found in 31 per cent. Cardiac and respiratory arrests were usually unrelated to each other and both frequently occurred without warning. Only 7 out of 71 patients with arrhythmias other than sinus tachycardia survived, compared with 15 out of 31 patients without them (P less than 0-005). During the latter part of the series when an arrhythmia computer was used to monitor 38 patients, it was shown that significantly lower arterial oxygen levels occurred in those with arrhythmias, other than sinus tachycardia, than in those without. They were also found to be more acidotic and hyperkalaemic, and a higher number required dialysis and ventilation. Macroscopical cardiac abnormalities including scattered petechial haemorrhages, small pericardial effusions, and fatty, pale, and flabby ventricles, were found at necropsy in 64 per cent of the patients examined. Combinations of these macroscopical abnormalities occurred, particularly in the paracetamol overdose group. Another necropsy finding of possible significance in the pathogenesis of arrhythmias was cerebral oedema, present in 48 per cent of the patients examined, and often associated with coning of the brain stem. However, 7 of the 16 patients who suffered asystolic cardiac arrests had no macroscopical abnormality of either heart or brain. In the management of patients with fulminant hepatic failure continuous cardiac monitoring is essential. Correction of the biochemical and coagulation defects may decrease the frequency of arrhythmias but studies of the mechanism and control of cerebral oedema and its relation to cardiovascular function are urgently needed.